Peripheral ameloblastoma: a case report - NAMDAR PEKİNER, FİLİZ MEDİHA (BRITISH INST RADIOLOGY, 2007)
Peripheral ameloblastoma, a rare and unusual variant of odontogenic tumour, comprises about 1% of all ameloblastomas. The extraosseous location is the peculiar feature of this type of tumour, which is otherwise similar to the classical ameloblastoma. An additional case of this infrequent tumour is described on the lingual alveolar mucosa of the right mandibular premolar region in a 60-year-old man. Clinical evidence, microscopic findings, CT imaging and recurrence for this tumour are discussed.
Keywords: peripheral ameloblastoma; odontogenic tumours; alveolar mucosa; mandible; BIOLOGICAL PROFILE; BUCCAL MUCOSA; NEOPLASM